In Defense of “Extreme Apriorism” - Rothbard, Murray N. (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2015)
In this article, the author develops an analysis of the methodological controversy between Fritz Machlup and Terence W. Hutchison. While Hutchison rejects the views of Ludwig von Mises and at the same time considers that Machlup does nothing but try to provide a methodological framework to Mises’ proposals, Machlup, by his turn, is located distant from Mises and near the positivist tradition in economic methodology. From the perception that both professor Mises and “extreme apriorism” remained without a proper defense in the debate, the author argues in defense of the Kantian apriorism endorsed by Mises.